Five years ago Jacobs age was 7 times that of his son and five years later the age of Jacob will be 3 times of his son. What are their present age?
By elimination method pls solve on paper and send fast guys
Answers
Answer:
Let the Jacobs age be X
And his sons age be y
After 5 years Jacobs age will be (X+5)
And his sons age will be (Y+5)
By condition 1:
(X+5)=3(Y+5)
X+5=3Y+15
3Y-X+10=0 .......(1)
Before5 years Jacobs age will be (X-5)
And his sons age will be (Y-5)
By condition 2:
(X-5)=7(Y-5)
X-5=7Y-35
7Y-X-30=0 ......(2)
X=3Y + 10 .......from (1)
Substituting the value of X in equation (2)
7Y-(3Y+10)-30=0
7Y-3Y-10-30=0
4Y = 40
Y= 10
Substituting the value of Y in equation 1.
3(10) - X+ 10=0
X=40
THEREFORE the age of Jacob =40 years
And age of his son = 10 years
Step-by-step explanation:
Answer:
The present age of Jacob is 40 years.
And the present age of son of Jacob is 10 years.
Step-by-step-explanation:
Let the present age of Jacob be x years.
And the present age of son of Jacob be y years.
Five years ago,
The age of Jacob = ( x - 5 ) years
And the age of his son = ( y - 5 ) years
From the first condition,
( x - 5 ) = 7 ( y - 5 )
⇒ x - 5 = 7y - 35
⇒ x - 7y = - 35 + 5
⇒ x - 7y = - 30 - - ( 1 )
Now,
Five years later,
The age of Jacob = ( x + 5 ) years
And the age of his son = ( y + 5 ) years
From the second condition,
( x + 5 ) = 3 ( y + 5 )
⇒ x + 5 = 3y + 15
⇒ x - 3y = 15 - 5
⇒ x - 3y = 10 - - ( 2 )
By subtracting equation ( 1 ) from equation ( 2 ), we get,
x - 3y = 10 - - ( 2 )
-
x - 7y = - 30 - - ( 1 )
(-).....(+).......(+)
______________
⇒ 4y = 40
⇒ y = 40 ÷ 4
⇒ y = 10
By substituting y = 10 in equation ( 2 ), we get,
x - 3y = 10 - - ( 2 )
⇒ x - 3 ( 10 ) = 10
⇒ x - 30 = 10
⇒ x = 10 + 30
⇒ x = 40
Now,
The present age of Jacob ( x ) = 40 years.
And the present age of son of Jacob ( y ) = 10 years.